2007
DOI: 10.1016/j.cca.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Do mutations causing low HDL-C promote increased carotid intima-media thickness?

Abstract: Background-Although observational data support an inverse relationship between high-density lipoprotein (HDL) cholesterol and coronary heart disease (CHD), genetic HDL deficiency states often do not correlate with premature CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
1
2
0
2
Order By: Relevance
“…30 The third study examined a limited number of American hypoalphalipoproteinemia patients, some of whom carry mutations in the LCAT gene; mean carotid IMT values were not different between hypoalphalipoproteinemia cases and controls. 31 These previous findings are clearly at variance with those found in the present study. The explanation for this discrepancy is not readily apparent, although it may be related to a distinctly lower prevalence of cardiovascular risk factors other than low HDL-C in the Italian LCAT-deficient families.…”
Section: Discussionsupporting
confidence: 68%
“…30 The third study examined a limited number of American hypoalphalipoproteinemia patients, some of whom carry mutations in the LCAT gene; mean carotid IMT values were not different between hypoalphalipoproteinemia cases and controls. 31 These previous findings are clearly at variance with those found in the present study. The explanation for this discrepancy is not readily apparent, although it may be related to a distinctly lower prevalence of cardiovascular risk factors other than low HDL-C in the Italian LCAT-deficient families.…”
Section: Discussionsupporting
confidence: 68%
“…In the present case, the haploinsufficiency was the likely result of the combination of a negative effect of the expressed mutant isoform resulting from protein termination (splice defect at exon 31) and post-translational instability as a byproduct of a poorly or non-functioning protein (splice defect at exon 7) based upon the predicted removal of 59 amino acids within the extracellular loop. In contrast to affected family members with premature CHD, the proband is clinically healthy despite low HDL-C, raising the possibility that in the absence of other CHD risk factors, isolated low HDL-C may not pose a substantially increased risk of vascular disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…atheroprotection or not. A life-long exposure to 30-60% reductions of HDL-C levels as a consequence of mutations in ABCA1 , APOAI , or LCAT has been reported to be associated with increased cIMT and CVD risk in several family studies (49,(158)(159)(160)(161)(162) but other investigators have not found this (163,164). The APOA1 Milano defect, leading to very low levels of HDL-C, has been associated with a normal cIMT in carriers (165).…”
Section: Cetpmentioning
confidence: 99%